Low-Cost Fabrication of High-Performance Fluorinated Polythiophene-Based Vis–NIR Electrochromic Devices toward Deformable Display and Camouflage - Wu, Zhixin; Zhao, Qi; Luo, Xiaoyu; Ma, Hude; Zheng, Wenqian; Yu, Jiawen; Zhang, Zhilin; Zhang, Kaiyue; Qu, Kai; Yang, Ruping; Jian, Nannan; Hou, Jian; et al. (Chemistry of materials, 2022)
Flexible electrochromic devices (FECDs) are extensively used in smart windows, deformable electronic displays, and wearable electronics. However, it remains very challenging to fabricate low-cost yet high-performance visible–near-infrared (vis–NIR) FECDs. In this work, we overcome this hurdle by developing a fluorinated polythiophene derivative with superior overall electrochromic performance and simple electropolymerization patterning. Fluorophenyl-modified polythiophene (band gap: 1.74 eV) can be readily synthesized via a one-step Grignard coupling with a high yield of >90% together with successive low-potential electropolymerization at 1.0 V vs Ag/AgCl. The intermolecular hydrogen bonding from the fluorine substitution of polythiophene backbones allows the facile electrodeposition of free-standing polymer films with a compact morphology and also leads to mechanical strength and electrical conductivity enhancement. Interestingly, such polymer films exhibit intriguing overall electrochromic performances with reversible color changes between deep red and light green upon doping/dedoping, including high optical contrast throughout the NIR region (max. 80% at 1600 nm), fast response time (0.93 s), high coloration efficiency (up to 752 cm2 C–1), outstanding stability against cycling (<3% reduction after 5,000 cycles), and excellent optical memory effect. The fabricated FECDs by electropolymerization patterning of such polymers display robust mechanical stability (<5% decay in optical contrast after 5,000 bending cycles with a bending radius of 1 cm) under a low driving voltage (0.85 V). We further demonstrate the applications of such patterned electrochromic devices toward deformable displays, color-changing electronic on-skin tattoos, and infrared camouflage with stable color-switching and robust mechanical properties.